2018
DOI: 10.1097/iop.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

In-Office Sutureless Correction of Prolapsed Subconjunctival Orbital Fat

Abstract: The authors propose an office-based, cost-effective, minimally invasive, sutureless technique for treating SOFP with local anesthesia in a safe and effective manner. The lack of complications or recurrence with an adequate follow-up period following this technique is encouraging. Surgeons should consider this technique in the surgical correction of SOFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Although the technique is relatively complicated and invasive, it is expected to prevent recurrence better than less invasive techniques that have been previously reported (Table 2), through the added procedure of connective tissue repair [5-9]. In the present study, no recurrence occurred, even in the six eyes with observation periods of more than five years; this potentially demonstrates the robust efficacy of the technique.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although the technique is relatively complicated and invasive, it is expected to prevent recurrence better than less invasive techniques that have been previously reported (Table 2), through the added procedure of connective tissue repair [5-9]. In the present study, no recurrence occurred, even in the six eyes with observation periods of more than five years; this potentially demonstrates the robust efficacy of the technique.…”
Section: Discussionsupporting
confidence: 58%
“…Patients are mostly male [1-4]. Recently, several surgical techniques for this disorder have been described, some of which are advocated as being minimally invasive [5-9]. However, knowledge of long-term results after such surgeries is still insufficient [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that SHOF in the superotemporal quadrant occurs in both eyes in more than half of the cases. [1–4,13] In our experience, 65.9% of cases of SHOF in the superotemporal quadrant were bilateral. In contrast, 12 of 15 cases (80.0%) with SHOF in other locations were unilateral.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have shown that more than 75% of patients with SHOF in the superotemporal quadrant were male. [2–4,6,7,9,14,15] In our experience, 40 out of the 44 patients (90.9%) with SHOF in the superotemporal quadrant were male. In addition, previous studies have shown that 38.5-76% of the cases were obese.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation